2013
DOI: 10.1160/th12-07-0518
|View full text |Cite
|
Sign up to set email alerts
|

Parallel overexpression and clinical significance of kallikrein-related peptidases 7 and 14 (KLK7 & KLK14) in colon cancer

Abstract: Currently available colon cancer (CC) markers lack sensitivity and specificity. Kallikrein-related peptidases (KLKs) present a new class of biomarkers under investigation for diverse diseases, including cancer. KLKs are co-expressed in various tissues participating in proteolytic cascades. KLK7 in human tumours facilitates metastasis by degrading components of the extracellular matrix. KLK14 promotes tumourigenesis by activating proteinase-activated receptors. In the present study we examined the concomitant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 49 publications
1
17
0
6
Order By: Relevance
“…Therefore, high mRNA expression of the KLK14 gene is most likely an independent predictor of poor prognosis in CLL. A similar prognostic role has been suggested for KLK14 expression in breast cancer [45] and colon cancer [20]. On the contrary, KLK14 has been suggested as a molecular biomarker of favorable prognosis in ovarian cancer [24].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Therefore, high mRNA expression of the KLK14 gene is most likely an independent predictor of poor prognosis in CLL. A similar prognostic role has been suggested for KLK14 expression in breast cancer [45] and colon cancer [20]. On the contrary, KLK14 has been suggested as a molecular biomarker of favorable prognosis in ovarian cancer [24].…”
Section: Discussionsupporting
confidence: 58%
“…In addition, low levels of KLK14 expression have been observed in many other human tissues, including breast, thyroid, kidney, colon, spleen, bone marrow, uterus, small intestine, and placenta [19]. Remarkable alterations in KLK14 mRNA expression have been noticed in several malignancies, including breast, ovarian, prostate, testicular, and colorectal cancer [19][20][21]. For instance, KLK14 mRNA expression is significantly upregulated in cancerous prostate specimens, especially in malignant tumors presenting high aggressiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Kallikrein peptidases are a family of serine proteases that are implicated in many complex proteolytic networks. Even if the exact physiopathological roles of KLKs in the development or in the progression of several diseases are still not completely elucidated, it is now well‐established that dysregulation of their activities could be associated with several pathophysiological disorders such as Netherton syndrome and cancers . Consequently, inhibition of this excessive proteolytic activity by small synthetic compounds as well as by polypeptidic inhibitors based on natural protein inhibitors might constitute a promising therapeutic strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Due to these mutations, the LEKTI could not effectively control the proteolytic activity of KLK5, KLK7, and KLK14, inducing inflammation and atopic‐like lesions in the skin . On the other hand, overexpression and activity of mostly all the KLKs were reported to be associated with pro‐cancer determinants . Implications of KLKs in several other pathologies, such as neurodegeneration, neuropsychological disorders, abnormal enamel formation of teeth ( amelogenesis imperfecta ), and so on were also reported.…”
Section: Structure Of Klk‐related Peptidasesmentioning
confidence: 99%
“…Thus, KLK7 may be an aberrantly expressed melanoma‐produced proteinase with tumorigenic functions and may represent a potential key element in melanoma progression. Although KLK7 has been described as a biomarker in many types of cancers (Devetzi et al ., ; Kryza et al ., ; Walker et al ., ), to our knowledge, this is the first report demonstrating a role for KLK7 in the metastatic process of melanoma. Our study showed that only 69% of the analyzed melanoma cell lines ectopically express KLK7 , whereas KLK14 and KLK6 are expressed by almost all of the cell lines.…”
Section: Discussionmentioning
confidence: 99%